Effect of nanofluid variable properties on natural convection in enclosures - Abu-Nada, Eiyad; Masoud, Ziyad; Öztop, Hakan Fehmi; Campo, Antonio (Elsevier France-Editions Scientifiques Medicales Elsevier, 2010)
In this work, the heat transfer enhancement in a differentially heated enclosure using variable thermal conductivity and variable viscosity of Al2O3-water and CuO-water nanofluids is investigated. The results are presented over a wide range of Rayleigh numbers (Ra = 10(3)-10(5)), volume fractions of nanoparticles (0 <= phi <= 9%), and aspect ratios (1/2 <= A <= 2). For an enclosure with unity aspect ratio, the average Nusselt number of a Al2O3-water nanofluid at high Rayleigh numbers was reduced by increasing the volume fraction of nanoparticles above 5%. However, at low Rayleigh numbers, the average Nusselt number was slightly enhanced by increasing the volume fraction of nanoparticles. At high Rayleigh numbers, CuO-water nanofluids manifest a continuous decrease in Nusselt number as the volume fraction of nanoparticles is increased. However, the Nusselt number was not sensitive to the volume fraction at low Rayleigh numbers. The Nusselt number demonstrates to be sensitive to the aspect ratio. It was observed that enclosures, having high aspect ratios, experience more deterioration in the average Nusselt number when compared to enclosures having low aspect ratios. The variable thermal conductivity and variable viscosity models were compared to both the Maxwell-Garnett model and the Brinkman model. It was found that at high Rayleigh numbers the average Nusselt number was more sensitive to the viscosity models than to the thermal conductivity models. (C) 2009 Elsevier Masson SAS. All rights reserved.
Keywords: Nanofluid; Viscosity; Thermal conductivity; Natural convection; Enclosure